Effect of Heat Input on Microstructure and Hardness Distribution of Laser Welded Si-Al TRIP-Type Steel - Adam Grajcar; Maciej Różański; Sebastian Stano; Aleksander Kowalski; Barbara Grzegorczyk (Advances in Materials Science and Engineering)
This study is concerned with issues related to laser welding of Si-Al type TRIP steels with Nb and Ti microadditions. The tests of laser welding of thermomechanically rolled sheet sections were carried out using keyhole welding and a solid-state laser. The tests carried out for various values of heat input were followed by macro- and microscopic metallographic investigations as well as by microhardness measurements of welded areas. A detailed microstructural analysis was carried out in the penetration area and in various areas of the heat affected zone (HAZ). Special attention was paid to the influence of cooling conditions on the stabilisation of retained austenite, the most characteristic structural component of TRIP steels. The tests made it possible to determine the maximum value of heat input preventing the excessive grain growth in HAZ and to identify the areas of the greatest hardness reaching 520 HV0.1.